2018
DOI: 10.1126/scitranslmed.aap9128
|View full text |Cite
|
Sign up to set email alerts
|

Prime and target immunization protects against liver-stage malaria in mice

Abstract: Despite recent advances in treatment and vector control, malaria is still a leading cause of death, emphasizing the need for an effective vaccine. The malaria life cycle can be subdivided into three stages: the invasion and growth within liver hepatocytes (pre-erythrocytic stage), the blood stage (erythrocytic stage), and, finally, the sexual stage (occurring within the mosquito vector). Antigen (Ag)-specific CD8+ T cells are effectively induced by heterologous prime-boost viral vector immunization and known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 58 publications
1
82
0
Order By: Relevance
“…In addition to their cytotoxic activity, CD8 Trm cells are efficient producers of proinflammatory cytokines that rapidly trigger both innate and adaptive protective immune responses (Schenkel et al, 2014). Thus, CD8 Trm cells are attractive targets for vaccine development against intracellular pathogens (Gola et al, 2018) and cancer immunotherapy (Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their cytotoxic activity, CD8 Trm cells are efficient producers of proinflammatory cytokines that rapidly trigger both innate and adaptive protective immune responses (Schenkel et al, 2014). Thus, CD8 Trm cells are attractive targets for vaccine development against intracellular pathogens (Gola et al, 2018) and cancer immunotherapy (Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…injected Plasmodium sporozoites does depend on the number of vaccine-induced CD8 T cells in the liver [22, 23, 58]. However, these previous studies are numerically inconsistent suggesting that either 3 × 10 4 [22] or 10 6 [23] memory CD8 T cells in the liver are needed for sterilizing protection. Further work is required to accurately quantify the number of T cells needed for protection.…”
Section: Discussionmentioning
confidence: 99%
“…Because liver stage is asymptomatic, removal of all liver stages prevents clinical symptoms of malaria and thus is highly desirable feature of an effective vaccine. Indeed, previous studies have shown that memory CD8 T cells are required for protection against a challenge with a relatively large number of sporozoites [14, 15] and that vaccination that induces exclusively memory CD8 T cells of a single specificity can mediate sterilizing protection against a sporozoite challenge [1623]. Antibodies and CD4 T cells may also contribute to protection in some circumstances, for example, following inoculation of sporozoites by mosquitoes in the skin [24, 25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He described a prime and target approach in which the boosting dose is administered intravenously, as opposed to intramuscularly, to increase efficacy by targeting CD8 + T cells to the liver. 23 In a field trial that used an intramuscular boosting dose, 67% efficacy, evaluated by polymerase chain reaction (PCR) positivity, was observed. 24 Hill is now look-ing at the feasibility of intravenous dosing in Africa to increase this efficacy.…”
Section: New Approaches To Malaria Vaccinesmentioning
confidence: 99%